Are attention deficit hyperactivity disorder symptoms stable irrespective of recovery from eating disorders? A 1‐year follow‐up of adult females. (6th October 2020) - Svedlund, Nils Erik; Norring, Claes; Ginsberg, Ylva; von Hausswolff‐Juhlin, Yvonne
Abstract: Objective: To explore the influence of recovery from eating disorders (ED) at 1‐year follow‐up on self‐reported attention deficit hyperactivity disorder (ADHD) symptoms in an unselected group of patients in a specialized ED clinic. Methods: Four hundred and eight adult females with an ED were assessed with the World Health Organization adult ADHD Self‐Report Scale‐Screener, and for comorbid psychiatric symptoms at baseline and 1‐year follow‐up. Recovery was registered at follow‐up. Results: ADHD symptoms decreased between baseline and follow‐up in recovered patients treated for bulimic ED. In not recovered patients, ADHD symptoms were stable. Decreased depressive symptoms were associated to decreased ADHD symptoms at 1‐year follow‐up. Conclusions: Bulimic ED and ADHD are linked together. This link, although not known in every detail, has clinical implications with possible value for bulimic ED patients. Clinical studies exploring implementation of ADHD treatment strategies for Bulimia Nervosa are recommended. Highlights: Attention deficit hyperactivity disorder (ADHD) symptoms decreased in patients recovered from eating disorders (ED). The decrease in ADHD symptoms was limited to patients recovered from bulimic ED. The results support the need to investigate whether stimulants are effective in treating Bulimia Nervosa.